Traumatic Memories of the Second World War and After
XV, 310 p. 1 illus. in color.
Keywords: This collection investigates the social and cultural history of trauma to offer a comparative analysis of its individual, communal, and political effects in the twentieth century. Particular attention is given to witness testimony, to procedures of personal memory and collective commemoration, and to visual sources as they illuminate the changing historical nature of trauma. The essays draw on diverse methodologies, including oral history, and use varied sources such as literature, film and the broadcast media. The contributions discuss imaginative, communal and political responses, as well as the ways in which the later welfare of traumatized individuals is shaped by medical, military, and civilian institutions. Incorporating innovative methodologies and offering a thorough evaluation of current research, the book shows new directions in historical trauma studies. .